2019
DOI: 10.1101/739599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RIP1 kinase mediates angiogenesis by modulating macrophages in experimental neovascularization

Abstract: word limit; 250)Inflammation plays an important role in pathologic angiogenesis. Receptorinteracting protein 1 (RIP1) is highly expressed in inflammatory cells and is known to play an important role in the regulation of apoptosis, necroptosis, and inflammation, however its role in angiogenesis remains elusive. Here, we show that RIP1 is abundantly expressed in infiltrating macrophages during angiogenesis, and genetic or pharmacological inhibition of RIP1 kinase activity using kinase-inactive RIP1 K45A/K45A mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…[ 37 ] Therefore, we first evaluated the stimulatory effect of HA‐PDA@Fe 3 O 4 on macrophages in vitro. Bone‐marrow‐derived macrophages obtained from Balb/c mice were induced to an M2‐like phenotype by interleukin‐4, [ 38 ] and then treated with HA‐PDA@Fe 3 O 4 , PDA@Fe 3 O 4 , or free HA for 24 h. Macrophage activation was evaluated using multicolor FCM and immunofluorescence staining. The macrophages exposed to HA‐PDA@Fe 3 O 4 , PDA@Fe 3 O 4 , or free HA upregulated M1‐related CD80 marker compared to that in the untreated control group (Figure S8a,b, Supporting Information), but simultaneously and significantly downregulated M2‐related CD206 marker, with HA‐PDA@Fe 3 O 4 being more efficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ] Therefore, we first evaluated the stimulatory effect of HA‐PDA@Fe 3 O 4 on macrophages in vitro. Bone‐marrow‐derived macrophages obtained from Balb/c mice were induced to an M2‐like phenotype by interleukin‐4, [ 38 ] and then treated with HA‐PDA@Fe 3 O 4 , PDA@Fe 3 O 4 , or free HA for 24 h. Macrophage activation was evaluated using multicolor FCM and immunofluorescence staining. The macrophages exposed to HA‐PDA@Fe 3 O 4 , PDA@Fe 3 O 4 , or free HA upregulated M1‐related CD80 marker compared to that in the untreated control group (Figure S8a,b, Supporting Information), but simultaneously and significantly downregulated M2‐related CD206 marker, with HA‐PDA@Fe 3 O 4 being more efficient.…”
Section: Resultsmentioning
confidence: 99%
“…For in vitro macrophage polarization study, bone marrow‐derived macrophages were first pretreated with interleukin‐4 (Sigma, Merck KGaA, Darmstadt, Germany) at a concentration of 50 ng mL −1 to induce the M2 phenotype, [ 38,58 ] and then incubated with free HA (14 µg mL −1 ), PDA@Fe 3 O 4 (100 µg Fe mL −1 ), or HA‐PDA@Fe 3 O 4 (100 µg Fe mL −1 ) for 24 h. After incubation, the macrophages were stained with the M1‐related marker anti‐CD80‐PE/Cy7 (Biolegend, cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…[RIPK]-regulated necrosis) that may be involved in photoreceptor degeneration. Mechanistic studies have revealed that blocking an individual cellular death pathway may activate another and vice versa 27,28,[80][81][82][83] . Furthermore, we have seen that different cellular death pathways may predominate in different cell types [28][29][30]81,82,84 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…For example, when ROS are the predominant cell death stimulus, ferroptosis (iron-dependent death) is the predominant pathway [87][88][89][90][91][92] ; whereas when tumor necrosis factor alpha (TNF-alpha) or FASL are the predominant stimuli, apoptosis and/or RIPK-dependent necrosis are the predominant pathways 24,25,31,32,86,[93][94][95][96] . To make things more complex, infiltrating immune cells also contribute to neurodegeneration via the inflammasome and cross-talk with several other pathways 80,85,[97][98][99][100][101][102][103][104][105][106] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…After corneal injury, neutrophils and macrophages infiltrate the cornea. Compared with other inflammatory cells, macrophages are presumed to be an important source of pro-angiogenic molecules, and they can support vascular endothelial sprouting (9,12,13). Furthermore, recent studies have revealed that the development of CNV can be suppressed by inhibiting macrophage infiltration but not neutrophil infiltration (14,15).…”
Section: Original Articlementioning
confidence: 99%